2022
DOI: 10.1002/ptr.7514
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide extract from Isatidis Radix inhibits multiple inflammasomes activation and alleviate gouty arthritis

Abstract: The polysaccharide extract from Isatidis Radix exhibits potent antiinflammatory and antiviral activities, but the mechanism of Isatidis Radix polysaccharide (IRP) remains obscure. Herein, we reported that IRP blocked the activation of nod‐like receptor pyrin domain‐containing 3 (NLRP3) inflammasome, leading to the inhibiting of caspase‐1 cleavage and IL‐1β secretion. Mechanistically, IRP did not inhibit NLRP3 inflammasome through suppressing mitochondrial reactive oxygen species (mtROS) production. However, IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Under in vitro conditions, IRP can inhibit caspase-1 cleavage and IL-1β secretion by blocking NLRP3 inflammasome activation. Under in vivo conditions, IRP can alleviate joint swelling caused by MSU crystals in mice and reduce the secretion of MPO, IL-6, IL-18, and IL-1β in the swollen joints [77].…”
Section: Isatidis Radix Polysaccharide (Irp) Extracted From Isatidismentioning
confidence: 96%
“…Under in vitro conditions, IRP can inhibit caspase-1 cleavage and IL-1β secretion by blocking NLRP3 inflammasome activation. Under in vivo conditions, IRP can alleviate joint swelling caused by MSU crystals in mice and reduce the secretion of MPO, IL-6, IL-18, and IL-1β in the swollen joints [77].…”
Section: Isatidis Radix Polysaccharide (Irp) Extracted From Isatidismentioning
confidence: 96%
“…The experimental study showed that Madecassoside alleviated MSU-triggered pad swelling, joint 99mTc uptake, and joint inflammation, which was accompanied with decreased expression of caspase-1, IL-1β and NLRP3 ( 100 ). The polysaccharide, extracted from Isatidis Radix , has a positive effect on alleviating GA. Mechanistically, polysaccharide suppressed the oligomerization of ASC and subsequently blocked the formation of NLRP3 inflammasome, which probably lead to the decreased ankle thickness and IL-1β, IL-18, IL-6, TNF-α and MPO secretion ( 101 ). Dioscin, an active ingredient, has been reported to have a protective effect against MSU-mediated inflammatory response in GA mouse model through inhibiting NLRP3 inflammasome and TLR4/NF-κB signaling pathway activation ( 102 ).…”
Section: Therapeutic Strategies For Targeting Nlrp3 In Gamentioning
confidence: 99%
“…This modulation aids in alleviating symptoms linked to MSU-induced gouty arthritis, such as neutrophil infiltration in knee joints, joint circumference and the production of TNF-α, IL-1β, IL-6, and IL-18. This effective inhibition of the NLRP3 signaling pathway is facilitated by this approach ( Ren et al, 2022 ). Furthermore, palmatine ( Cheng et al, 2022 ), rhein ( Chang et al, 2019 ), berberine ( Zheng et al, 2023 ), dihydroberberine ( Xu et al, 2021 ), celastrol ( Yan et al, 2021 ), tanshinone IIA ( Xu et al, 2022b ), total saponin of Dioscorea polystachya Turcz.…”
Section: Signal Pathways Of Tcm Modulating Gout Pathological Progressionmentioning
confidence: 99%
“…Through its modulation of the NLRP3 signaling pathway, scutellarin can enhance renal damage caused by UA (Li et al, 2020b). Tetrahydropalmatine, a primary bioactive compound with analgesic, anti-addictive, anti-inflammatory, neuroprotection, and anticancer activities (Du et al, 2022) approach (Ren et al, 2022). Furthermore, palmatine (Cheng et al, 2022), rhein (Chang et al, 2019), berberine (Zheng et al, 2023), dihydroberberine (Xu et al, 2021), celastrol (Yan et al, 2021), tanshinone IIA (Xu et al, 2022b), total saponin of Dioscorea polystachya Turcz.…”
Section: Nlrp3 Signal Pathwaymentioning
confidence: 99%